2022
DOI: 10.3390/agronomy12102239
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Cotton Production through Increased Competitiveness: Analysis of Comparative Advantage and Influencing Factors of Cotton Production in Xinjiang, China

Abstract: Cotton production makes an important contribution to the income of rural residents and the economy in Xinjiang province, which leads other provinces in terms of planted area, total production, and average yield of cotton in China. This study analyzed the competitiveness of cotton production in the study area using the efficiency advantage index (EAI), scale advantage index (SAI), and aggregated advantage index (AAI). Moreover, the factors influencing the productivity of cotton have been investigated by the use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 35 publications
0
4
0
1
Order By: Relevance
“…Excluding the water quality of irrigation, such as brackish water, magnetized water, etc., we screened scholars' published journal papers and master's doctoral dissertations from 1 January 1960 to 31 December 2022. According to the needs of the research topic, the literature screening for inclusion needed to meet the following criteria: (1) the test site should be a field trial within the scope of Xinjiang, potting and indoor trials should be excluded, and the test object should be cotton; (2) the number of trial replicates should be ≥3; (3) cotton yields recorded in the study cases were seed cotton yields; (4) multiple replicated observations under the same treatment were averaged; (5) when there were studies with additional factor effects in the trials, they were considered as independent trials separately included in the database; (6) for multi-year experimental studies in the same region in the literature, they were considered to be mutually independent trials separately included in the database. In addition, based on scholars' studies on deficit irrigation in Xinjiang [37,42,43], this study defined the range of complete irrigation (full irrigation) as between 368 and 425 mm, and the irrigation amount below this range was considered as deficit irrigation and classified into three levels (40~60% FI, 60~80% FI, and 80~100% FI, FI being the fully irrigated level).…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Excluding the water quality of irrigation, such as brackish water, magnetized water, etc., we screened scholars' published journal papers and master's doctoral dissertations from 1 January 1960 to 31 December 2022. According to the needs of the research topic, the literature screening for inclusion needed to meet the following criteria: (1) the test site should be a field trial within the scope of Xinjiang, potting and indoor trials should be excluded, and the test object should be cotton; (2) the number of trial replicates should be ≥3; (3) cotton yields recorded in the study cases were seed cotton yields; (4) multiple replicated observations under the same treatment were averaged; (5) when there were studies with additional factor effects in the trials, they were considered as independent trials separately included in the database; (6) for multi-year experimental studies in the same region in the literature, they were considered to be mutually independent trials separately included in the database. In addition, based on scholars' studies on deficit irrigation in Xinjiang [37,42,43], this study defined the range of complete irrigation (full irrigation) as between 368 and 425 mm, and the irrigation amount below this range was considered as deficit irrigation and classified into three levels (40~60% FI, 60~80% FI, and 80~100% FI, FI being the fully irrigated level).…”
Section: Data Collectionmentioning
confidence: 99%
“…Cotton cultivation in China is mainly distributed in the Yangtze River Basin, the Yellow River Basin, and the northwestern interior. In recent years, with the reduction in cotton planting areas in the Yangtze River and Yellow River basins, Xinjiang has become the largest cotton area in China [ 2 ]. The cotton production in Xinjiang accounts for about 90.2% of the total national production [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Begitupun sebaliknya semakin rendah harga barang yang ditawarkan semakin sedikit [12]. Menurut Kotler dan armstrong mendefinisikan bahwa harga adalah jumlah dari semua nilai-nilai yang konsumen tebus sehingga mendapat manfaat dari memiliki atau menggunakan barang atau jasa [13]. Produktivitas adalah perbandingan antara hasil yang dicapai (keluaran), dengan keseluruhansumber masukan, yang dipergunakan persatuan waktu.…”
Section: Pendahuluanunclassified
“…The global cotton market has an estimated value of over $44 billion, and in the US alone, official estimates indicated that cotton provides an annual revenue of over $21 billion, employing over 125,000 people [5,6] . In China, cotton is grown in about 70% of the 35 provinces, employing almost 300 million people [7] . This background emphasizes the importance of cotton to the global economy.…”
Section: Introductionmentioning
confidence: 99%